Performance Appraisal and Employee Performance in National Agency for Science and Engineering Infrastructure Institutes (NASENI) in South East, Nigeria - Ogala, Blessing A.; Igwe, Nick N.; Anichebe, Nnaemeka A.; Chukwu, Christian U.; Oparah, Frank; Obodoagu, Kenneth Ogomegbunam (Archives of Business Research, 2024)
This study sets out to fulfil two objectives: to establish the association between contextual performance in NASENI and feedback from evaluations, and the relationship between employees’ training and counterproductive behaviour in the surveyed organization. The theoretical underpinning used was the resource-based view which underscored the importance of putting qualified employees in the proper positions through periodical evaluations. This would enable the organization acquire competitive advantages over time. The study used a descriptive survey design to collect data. The total population of the study was 710 (seven hundred and ten respondents). Sample size determination was performed using Yamane Formula. Instrument for data collection was the questionnaire. The questionnaire was divided into two distinct sections: The employee bio data and the relationship between the dependent variable and independent variables respectively. Findings revealed that evaluation feedback significantly affects contextual performance and that employee training significantly reduces counterproductive behaviour in NASENI. The implication of these findings is that evaluation feedback in performance appraisal and employee training on counterproductive behaviour in NASENI have the capacity of increasing performance in organizations especially in organizations where employees have been accused of poor performance with low revenue yielding to the Federal government.